On the Role of Density‐Driven Dissolution of CO2 in Phreatic Karst Systems. Issue 12 (16th December 2021) - Class, H.; Bürkle, P.; Sauerborn, T.; Trötschler, O.; Strauch, B.; Zimmer, M.
Abstract: Density‐driven dissolution of carbon dioxide in water is a well‐known and much described mechanism in geological sequestration of this greenhouse gas. It is remarkable that such enhanced dissolution does not receive attention in karst hydrology and speleology. Models and hypotheses on karst development are complex and consider many different processes. We focus here on the influence of CO2 partial gas pressures at the interface between atmosphere and karst water on the dynamics of dissolved CO2 concentrations below the water table. Seasonal variations of microbial soil activity and root respiration or barometric‐pressure changes cause fluctuations in CO2 partial pressures. Dependent on the existence and strength of a karst‐water background flow, fingering regimes might be triggered causing enhanced dissolution of CO2 . This allows replenishment of CO2, and, thus, dissolutional power even deep in the water body without the need for percolating water to transport dissolved CO2 . We present and discuss simplified and generic experimental and computational scenarios to strengthen our claim, and we try to give answers to: how much? and under which circumstances? The applied numerical model solves the Navier‐Stokes equation with water density dependent on CO2 concentration and temperature. We show that calculated CO2 mass fluxes into the water bodies are dependent on the ratio of Péclet to Rayleigh numbers (Pe/Ra) and show a local minimum around Pe/Ra = 1, i.e. when natural and forced convection are about equal. Concluding, we claim that there is sufficient reason to consider density‐driven dissolution as a process of relevance in karstification if circumstances are given. Plain Language Summary: Karst systems form in rocks, such as limestones, that are soluble in the presence of water charged with carbonic acid. The carbon dioxide (CO2 ) can take different pathways to replenish dissolutional power in karst water. This study discusses a pathway that did not receive much attention yet. The density of water increases when CO2 dissolves, and, when dissolution occurs at the water table, instabilities may be induced. This can trigger fingering‐like flow and enhance the rate of dissolution at the water table. The phenomenon is well‐known as a major trapping mechanism for CO2 injected into geological formations for mitigating greenhouse‐gas emissions. The more so is it remarkable that the same phenomenon is not discussed in karst hydrology and speleology. Of course, the different conditions of concentrations, pressures, and temperatures require attention. For realistic conditions, we demonstrate experimentally and by numerical simulations that density‐induced transport of CO2 is significant. The lab experiment used a 6 m long vertical column and imitates an analog to a cave lake. We can see that within a few months time, significant amounts of CO2 can be dissolved at karst‐typical elevated gaseous CO2 concentrations. The influence of natural ground‐/karst water background flow is addressed by numerical simulations. Key Points: Density‐driven CO2 dissolution is a process that deserves more attention in karstification theories and beyond Fluctuating CO2 partial pressures in the vadose zone can enhance dissolution of CO2 in phreatic karst water Generic scenarios are used to demonstrate how density‐driven dissolution can contribute to replenishing CO2 in karst water